Determinants of tax burden in Cote d'Ivoire - Fofana, Yacouba (KDI School, 2011)
We sometimes wonder, with the given situation of developing countries, if it is possible to increase taxes levy as part of a stabilization program or mobilize significant resources to finance a development program. These questions will be answered in the analysis of the determinants of tax burden. The analysis is done through a simple linear model estimated with ordinary least squares method with secondary data covering the period 1970-2007 for Cote d'Ivoire. We come to the conclusion that money supply and investment are important variables in determining the tax burden. Contrary to previous studies, per capita income and economic openness to the outside appeared as less explanatory variables of tax deductions in Cote d'Ivoire. Beside these macroeconomic variables we can also add the idea of reforming the tax administration to reduce fraud and make tax collection process more efficient.
Thesis(Master) --KDI School:Master of Public Policy,2011